Ensino de ciências da natureza e matemática: perspectivas de inclusão escolar em aulas de ciências da natureza e matemática em uma escola do interior paulista - Souza Neto, Osório Augusto de (Universidade Federal de São Carlos, 2019)
This research was carried out through the technique of Single Case Study in a school in the interior of the state of São Paulo. Through a mixed approach, from the perspective of Discursive Textual Analysis and Textual Statistical Analysis, carried out with the aid of NVivo (2017) and IRAMUTEQ (2014) softwares, we sought to verify if the Collective Pedagogical Work Classes (CPWCs) provide (or not) elements for inclusive classes in Natural Science and Mathematics for students with special educational needs (SEN). In this same context, it was evidenced that the demands arising from DE regarding the subjects to be treated in CPWCs generate negative impacts in relation to the school's articularities, as well as in the continuing education of teachers, in a true implementation of a government policy. In addition, it was possible to show that the lack of public resources for the payment of daily fees to DE technicians, to provide training for teachers and Pedagogical Coordinating Teachers (PCTs) in the researched school, has negative impacts in relation to teacher education, making inclusion not fully possible for students with SEN. According to the concept of SEN adopted in this work, the study presented that although it is only a snippet of what happens in the school throughout the year, the perspective for inclusive classes in Natural Sciences and Mathematics for students with SEN is poor. The factors that preclude the mentioned perspectives show, among other elements, the need for changes in the spatial accessibility structures and the comprehension about what students with SEN are, commonly treated as if they were target of Special Education. Moreover, it was possible to infer that the non-collective construction of the school's Political Pedagogical Project (PPP) has implications that do not corroborate the inclusion of students with SEN. Likewise, the large number of students in each class, the attitudinal barriers brought by some teachers, and the mismanagement of financial resources available to the school make the process of inclusion for students with SEN in nature science and mathematics classes prone to failure.
Natural sciences and math teaching: scholar inclusion's perspectives in natural science and math classes in a São Paulo state school
Keywords: Ciências da natureza; Matemática; Necessidades educacionais especiais; Inclusão escolar; Formação continuada de professores; Natural sciences; Mathematics; Special educational needs; School inclusion; Continuing teacher training; CIENCIAS HUMANAS::EDUCACAO